DÉFINIR LE STATUT URBAIN EN ROUMANIE À L’AIDE DES CRITÈRES PERTINENTS - IONEL MUNTELE (Revue Roumaine de Géographie)
The definition of the urban status in Romania between the pertinent criterias. This study, presented in the „Dimitrie Cantemir” scientifical seminary of Iaşi, in 2008, is one analysis aboutthe differences into official vision (administratively) of urban status and statistical image of the functionality and the demographical potential of the Romanian settlements. The declared intention is the identification of a possible point of depart in remapping, in the scientifical interest, of the spatial deficitary urban network and its deficiently use in the administrativ-territorial division of the country.